2020
DOI: 10.3390/su12176878
|View full text |Cite
|
Sign up to set email alerts
|

What Motivates Users to Keep Using Social Mobile Payments?

Abstract: Due to the rapid diffusion of social mobile payment (SMP), the current research explores the post-adoption behavior of SMP users. It proposes a research model to determine the core predictors of users’ continuance intentions to use SMPs. Through the analysis of survey data from South Korea, it indicates that satisfaction strongly and positively affects users’ continuance intentions. Moreover, satisfaction is influenced by perceived usefulness (PU), security, and enjoyment. Interestingly, although perceived eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 64 publications
2
23
1
Order By: Relevance
“…Second, we demonstrated that PEU only indirectly (i.e., the direct effect was not supported by our data) influenced ATT through the mediating effect of PU. These results concord with those of several studies ( Nan et al., 2020 ; Slade et al., 2015 ), which reported that when users are skillful in the use of a product/service, the role of PEU in the perceptions of these skillful users is not strong. Hence, users that are proficient in the use of a technology do not care much about its PEU ( Nan et al., 2020 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Second, we demonstrated that PEU only indirectly (i.e., the direct effect was not supported by our data) influenced ATT through the mediating effect of PU. These results concord with those of several studies ( Nan et al., 2020 ; Slade et al., 2015 ), which reported that when users are skillful in the use of a product/service, the role of PEU in the perceptions of these skillful users is not strong. Hence, users that are proficient in the use of a technology do not care much about its PEU ( Nan et al., 2020 ).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, Davis (1989) argued that individuals tend to have positive PU toward specific technologies when they find the technologies easy to use, a viewpoint that has been supported by some research ( Hsieh and Lai, 2020 ; Nan et al., 2020 ;Yuen et al., 2020). For example, Nan et al. (2020) analyzed data from 205 Korean users to show that PEU enhances PU regarding mobile payments.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 93%
“…Some of the major contributions of fintech are reduction of transaction costs, improvement of service quality, and preparation of innovative measures to offer financial services [20,21]. To be precise, MPS enables users to easily purchase goods and services by just entering their passwords, PINs, and biometric authentications, with there being no stress to insert personal information for each of the transactions [22][23][24]. Table 1 provides a list of the characteristics of the most commonly used MPSs in Korea [25].…”
Section: Fintech-enabled Mobile Payment Servicesmentioning
confidence: 99%
“…Based on distinguishing pre-and post-adoptive stages of acceptance, ECM enlightens the formation of the continued use of IT by new variables, appropriate in multiple settings, including e-learning, online services, mobile banking, e-commerce and social network usage (Shaikh & Karjaluoto, 2015). Research on continuance has widely applied solely ECM or integrated with other theories and frameworks such as TAM (e.g., Boakye et al, 2014;Joia & Altieri, 2018;Nan et al, 2020), theory of reasoned action (TRA) and theory of planned behaviour (TPB) (e.g., Cenfetelli et al, 2008;Liang et al, 2013), UTAUT and UTAUT2 (e.g., Lu, 2014;Venkatesh et al, 2003Venkatesh et al, , 2011Zhao & Bacao, 2020), diffusion of innovation theory (DIT) (e.g., Joia & Altieri, 2018;Lin, 2013), selfdetermination theory (SDT) (e.g., Roca & Gagné, 2008;, effort-accuracy model (EAM) (Ashraf et al, 2020) and Information system (IS) success model (Gao et al, 2015;L. Wang et al, 2019;Zhou, 2013).…”
Section: Continuance In M-shoppingmentioning
confidence: 99%